Perbandingan Kinerja Metode Klasifikasi Chi-square Automatic Interaction Detection (CHAID) dengan Metode Klasifikasi Algoritma C4.5 pada Studi Kasus : Penderita Diabetes Melitus Tipe 2 Di Samarinda Tahun 2015 - Muhammad Faisal; Yuki Novia Nasution; Fidia Deny Tisna Amijaya (Program Studi Statistika FMIPA Universitas Mulawarman, 2017)
C4.5 algorithm is tree classification where tree branches can be more than two. In C4.5 algorithm, the decision tree is based on entropy and gain criterias. Chi-Squared Automatic Interaction Detection (CHAID) classification method is a methods which is used to divide data to become a smaller groups based on categorical dependent and independent variables. The purpose of this research is to determine the classification process by C4.5 algorithm and CHAID method for DM type 2 patients. Risk factors for diabetes type 2 are Decline, Age, Gender, Status of Obesity, Diet, and Sports Activity based on the availability of source data from the Hospital of Abdul Wahab Sjahranie Samarinda. The results show that factors which significantly affect the DM type 2 patients are Obesity and Sport Activity. While by using CHAID, the factors which significantly affect the patients are Decline, Obesity, Diet and Sports Activity. The Classification result accuracy of the C4.5 algorithm is 90% and 94% for CHAID method.